2007
DOI: 10.1016/s0140-6736(07)60074-9
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in China: results of a national surveillance programme

Abstract: The results suggest that a range of unique biological and social forces are driving the spread of syphilis in China. A national campaign for detection and treatment of syphilis, and a credible prevention strategy, are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
262
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(272 citation statements)
references
References 27 publications
5
262
0
2
Order By: Relevance
“…First, the study was only implemented in 6 urban regions located in South China, and care must be taken when generalizing the findings to other areas. At the same time, other research has suggested that China's primary and secondary syphilis cases are substantially greater in urban regions than in rural areas [13,15] Second, although every effort was made to make the intervention and control groups as comparable as possible, they were not identical. The intervention group had a higher syphilis prevalence than the control group at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the study was only implemented in 6 urban regions located in South China, and care must be taken when generalizing the findings to other areas. At the same time, other research has suggested that China's primary and secondary syphilis cases are substantially greater in urban regions than in rural areas [13,15] Second, although every effort was made to make the intervention and control groups as comparable as possible, they were not identical. The intervention group had a higher syphilis prevalence than the control group at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Reported primary and secondary syphilis cases have increased over the past 5 years in many parts of South China [13][14][15]. The study took place from June 2009 to March 2011 in 6 southern cities: Jiangmen and Maoming in Guangdong Province, Wuzhou and Hezhou in Guangxi Province, and Qionghai and Sanya in Hainan Province (Figure 1).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The congenital syphilis (CS) incidence in China increased from 0.01 per 100 000 live births in 1991 to 19.7 per 100 000 live births in 2005, 1 resulting in an average of more than one syphilitic neonatal birth per hour in 2008. 2 The Chinese Ministry of Health recently announced a comprehensive 10-year National Syphilis Prevention and Control Plan (NSCP), which aimed to reduce the number of newly reported CS cases to less than 30 per 100 000 live births by 2015 and continuously reduce the number to 15 per 100 000 live births by 2020.…”
Section: Received 1 August 2014 Accepted 10 September 2014 Publishementioning
confidence: 99%
“…In recent years, syphilis has reemerged as a significant public health problem in many countries, including China. Nationwide surveillance data indicate that the incidence rate of syphilis in China in 1993 was 0.2 per 100,000 persons, whereas that for primary and secondary syphilis was 5.7 per 100,000 persons in 2005 (1). According to nationwide surveillance data, there were 327,433 new cases of syphilis in China in 2009 (24.7 per 100,000 persons).…”
Section: Introductionmentioning
confidence: 99%